The Economic Factors Influencing Exchange rate of Lao Kip (LAK) against the Thai Baht (THB) - PHOUNNALY , Phayvanh; VATTHANA , Mongkhoun; PHENGSAVAT, Sitthivikone (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
This research aimed to investigate the economic factors that influence exchange rate of LAK against the THB. The researcher used the quarterly data from the database of the Bank of Lao. PDR and Bank of Thailand in the period of 2011-2020 (40 quarters) by testing the economic factors influencing exchange rate of LAK against the THB in long-term period by applying the Engle and Grenger method and short-term through the Error Correction Model. The results found that the fluctuation in exchange rate of LAK against the THB in long-term was positively influenced by economic factors, which consisted of four factors such as: 1) the minimum loan rate differential, which LAK depreciated against the THB, 2) the change of money supply differential, which LAK depreciated against the BATH, 3)the inter-bank rate differential, which LAK appreciated against the BATH and 4) the change of export differential, which LAK appreciated against the BATH. The fluctuation in exchange rate of LAK against the THB in short-term was positively influenced by economic factors, which consisted of four factors such as: 1) the change of minimum loan rate differential, which LAK depreciated against the THB, 2) the change of money supply differential, which LAK depreciated against the THB, 3) the exchange rate of LAK against THB in the last quarter, which LAK depreciated against the THB and 4) the change of export differential, which LAK appreciated against the THB and The short-term equilibrium deviates to the long-term equilibrium with a velocity of 53.10%. Therefore, in implementing the government’s fiscal policy and monetary policy, shifting of economic factors in both Lao and Thailand to should be taken into consideration.